2015
DOI: 10.1002/lary.25726
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and management of Fanconi anemia patients with head and neck cancer: A 10‐year follow‐up

Abstract: Objective To describe the management and outcomes of Fanconi anemia (FA) patients with head and neck squamous cell carcinoma. Study Design Cohort study. Methods Demographic information, prognostic factors, therapeutic management, and survival outcomes for FA patients enrolled in the International Fanconi Anemia Registry (IFAR) who developed head and neck squamous cell carcinoma (HNSCC) were analyzed. Results 35 FA patients were diagnosed with HNSCC at a mean age of 32 years. The most common site of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 45 publications
4
100
0
Order By: Relevance
“…While variability occurs, recurrent features include developmental anomalies and malformations, most commonly growth retardation, cutaneous pigment displacement, and radial ray defects. Other frequent aspects of FA comprise early-onset bone marrow failure and cancer predisposition, specifically for acute myelogenous leukemia and head and neck squamous cell carcinoma (1)(2)(3)(4). FA results from faults in the FA/BRCA pathway for DNA interstrand cross-link (ICL) repair, in which proteins encoded by 21 FA genes reported thus far -designated as or aliased with the prefix FANC-and serial letters of the alphabet, FANCA to FANCV -and associated proteins interact (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…While variability occurs, recurrent features include developmental anomalies and malformations, most commonly growth retardation, cutaneous pigment displacement, and radial ray defects. Other frequent aspects of FA comprise early-onset bone marrow failure and cancer predisposition, specifically for acute myelogenous leukemia and head and neck squamous cell carcinoma (1)(2)(3)(4). FA results from faults in the FA/BRCA pathway for DNA interstrand cross-link (ICL) repair, in which proteins encoded by 21 FA genes reported thus far -designated as or aliased with the prefix FANC-and serial letters of the alphabet, FANCA to FANCV -and associated proteins interact (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in FANCB are associated with genetic instability and hypersensitivity to DNA crosslinking agents such as platinumderivatives (33), both of which are also hallmarks of HNSCC cells. Remarkably, all FA patients including FANCB patients have an extremely high incidence of spontaneous HNSCCs (21)(22)(23). Importantly, other groups demonstrated that FANCB can be significantly down-regulated in sporadic HNSCC (40) and that up to 31% of sporadic HNSCC tumors demonstrate hypermethylation of the FANCB promoter locus (41).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, SCCs of the head, neck, and esophagus and in women also vulvar and cervical cancers occur at astonishingly high rates in FA patients, up to 14% of patients by 40 years of age (21)(22)(23). This strongly suggests that defects in the FA pathway might increase the risk of developing HNSCCs.…”
mentioning
confidence: 99%
“…Moreover, solid tumors tend to develop later in the course of disease. Median age of onset of solid tumors is around 30 years in literature 43 . But in our part of world patients hardly cross the age of 20 years, mainly because of limited availability of bone marrow transplant and other health facilities.…”
Section: Discussionmentioning
confidence: 99%